A importância do Sistema Único de Saúde como política pública democrática no contexto do Direito brasileiro - Portolese, Júlia Teixeira (2023)
The present thesis intends to know and explore themes such as creation of Brazilian Unified Health System in compliance with Federal Constitution of 1988; history of systems’ creation in Brazil; limits to guarantee health right; tensions between universal and individual health rights; public health and its social management; definition and principles of an efficient Unified Health System; actions and main modalities of public health policies in Brazil; competences’ division of federal entities for effectiveness of Unified Health System medicine policy on Federal Constitution; implementation of public policy cycles; Unified Health System public budget and constitutional provision for its funding; plan and budget of National Health Fund and discussion about existential minimum and possible reserve in this sector; democracy on Unified Health System its theories, concepts and modalities of social participation; social management of health within the scope of Unified Health System; public administration reforms and its management model in Brazil; development of citizenship rights on Unified Health System; popular participation and control by society with the aim of fulfilling guarantee of access to health. This policy benefits social inclusion of marginalized members’ society by broadening ways of provide services and supplying essential products, as well as demonstrate the Judiciary, through its attributions is capable of realize collective or individual human and fundamental rights of citizen guaranteed in the Brazilian Constitution of 1988. In the end, after discuss issues mentioned above, we will verify about an existence and fulfillment of duty related to a better efficient Unified Health System with other federative and non-federal entities, whether or not they meet the guarantee of public policy for hyposufficients and all who need it to realize healths’ right